Poesia para existir e resistir: a experiência de escolas que desenvolvem saraus na educação básica do município de São Paulo - Santino, Paula Renata S. Gomes (2020)
The present research aimed to investigate, based on the references of the critical theory of society, especially the concepts of autonomy and cultural formation of TW Adorno, the experience of public schools that develop soirees in the city of São Paulo, their presence in school curricula and in Political Pedagogical Projects. Two schools belonging to the Regional Directorate of Campo Limpo, in the city of São Paulo / SP, were studied in order to identify how the soirees develop in their curricula and how they are related to other pedagogical actions; interactions between students and teachers and between students themselves were also analyzed. Considering that the presence of soirees in the schools of the DRE Campo Limpo is the result of the growth of cultural and artistic actions carried out by collectives of popular and peripheral culture in this territory, it was sought to identify, through the observation of soirees promoted by the selected institutions, if In fact, their realization was incorporated as an element of the identity of the school unit and how the possibilities of working with them are developed in the school routine. The data produced in the empirical research allow us to affirm that the soirées, used as a methodological resource and curricular content, produce a trend that allows an environment and a space for the cultural and political formation of those involved through experience with art, poetry and peripheral literature